Hamster and gerbil - Coppendale, Jean. (Irvine, CA : QEB Pub., 2004)
Offers advice to first-time pet owners on how to care for a gerbil or hamster, providing a list of supplies, discussing handling, feeding, cleaning, and playing, and touching on the topic of pet death.
Includes index.
6.4
3-6
Keywords: Gerbils as pets -- Juvenile literature; Hamsters as pets -- Juvenile literature; Gerbils; Hamsters; Pets; Gerbils; Hamsters; Pets; Hamsters; Gerbils; Pets